A Novel Concept for Unidirectional Communication With an Active Implant Based on Deliberately Produced Human Body Signals. - Benke, Elisabeth; Preis, Alexander; Schulz, Alisa; Reitelshöfer, Sebastian; Franke, Jörg (Annual International Conference of the IEEE Engineering in Medicine and Biology Society, 2022)
A new patient-friendly and discrete approach to build a unidirectional communication path with active implants based on deliberately produced human body signals is presented. The application for which this approach is intended is an artificial urinary sphincter implant, the closure mechanism of which is wirelessly actuated in the event of micturition need. Conventional implant communication methods can be associated with limitations regarding technological implementation and usability, and are used by medical professionals only. In order to enable patients to discretely and directly communicate with their implant without the need for an external handheld device, the feasibility of a communication approach based on manually applied 'knocking' signals on abdominal tissue is examined in the presented work. A gelatin-based phantom model is used to mimic vibro-acoustic properties of human soft tissue in vitro. A piezoelectric element and an electret microphone are applied as sensors for signal detection at the implantation site and are investigated with respect to their suitability for the intended application. Clinical Relevance- The presented implant communication method can contribute to urinary incontinence therapy by enabling patients to discretely and user-friendly actuate their artificial sphincter implant and can provide a basis for future research into new implant communication technologies.
Keywords: Urinary incontinence; medical implant; implant communication